The idea of a university : defined and illustrated - Newman, John Henry, 1801-1890. (London : Routledge/Thoemmes Press, 1994)
Introductory. Theology a branch of knowledge. Bearing of theology on other knowledge. Brearing of other knowledge on theology. Knowledge its own end...
Keywords: Newman, John Henry, -- 1801-1890.; Education; Higher education; Education phylosophy; Aims and objectives; Newman, John Henry, -- 1801-1890.; Education, Higher -- Aims and objectives; Education philosophy